Decadal changes in radiative fluxes at land and ocean surfaces and their relevance for global warming. (2nd November 2015) - Wild, Martin
Abstract : Anthropogenic interference with climate occurs primarily through modification of radiative fluxes in the climate system. Increasing releases of greenhouse gases into the atmosphere lead to an enhancement of thermal radiation from the atmosphere to the surface by presently about 2 W m −2 per decade, thereby causing global warming. Yet not only thermal radiation undergoes substantial decadal changes at the Earth surface, but also incident solar radiation (SSR), often in line with changes in aerosol emissions. Land‐based observations suggest widespread declines in SSR from 1950s to 1980s ('global dimming'), a partial recovery ('brightening') since mid‐1980s, and indication for an 'early' brightening in 1930s and 1940s. No similar extended observational records are available over oceans. However, modeling studies, conceptual frameworks and available satellite‐derived records point to the existence of decadal SSR variations also over oceans. SSR changes overall match with decadal variations in observed warming rates, suggesting that SSR variations may effectively modulate greenhouse gas‐induced warming. Specifically, on the Northern Hemisphere, the lack of warming from 1950s to 1980s and its subsequent acceleration in the 1990s fits to the trend reversal from dimming to brightening and associated changes in air pollution levels. From the 1950s to 1980s no warming was also observed over Northern Hemispheric Oceans, in line with conceptual ideas that subtle aerosol changes in pristine ocean areas, effectively amplified by aerosol–cloud interactions, can substantially alter SSR, thereby modulating Sea Surface Temperatures. On the Southern Hemisphere, the absence of significant aerosol levels fits to the observed stable (greenhouse gas‐induced) warming rates since the 1950s. WIREs Clim Change 2016, 7:91–107. doi: 10.1002/wcc.372 This article is categorized under: Paleoclimates and Current Trends > Modern Climate Change